(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Teacher research plays an increasingly significant rolein contemporary society as a basis for self-exploration and inquiry. For thelast few decades there have been active scholarly efforts to formalizeself-study research as an accepted form of inquiry and further the framework asa promising research paradigm in educational research. For instance, Self-Studyof Teacher Education Practices (S-STEP) Special Interest Group of the AmericanEducational Research Association (AERA) has promoted theoretical discussions onself-study. Recently, the discussion has been expanded to include acomprehensive methodology of self-study as well as strategies and techniques usefulto conduct a self-study (Lassonde, Galman, & Kosnik, 2009; Pinnegar &Hamilton, 2009). Self-study that uses a systematic process for inquiry such asthe action research process (Mertler & Charles, 2008; Mills,2003)—particularly where researchers use processes to identify a problem andexplore how to address the problem in authentic contexts—can provide valid,reliable, and systematic protocols for classroom inquiry.